2018
DOI: 10.1186/s12870-018-1430-2
|View full text |Cite
|
Sign up to set email alerts
|

The key genes and pathways related to male sterility of eggplant revealed by comparative transcriptome analysis

Abstract: BackgroundMale sterility (MS) is an effective tool for hybrid production. Although MS has been widely reported in other plants, such as Arabidopsis and rice, the molecular mechanism of MS in eggplant is largely unknown. To understand the mechanism, the comparative transcriptomic file of MS line and its maintainer line was analyzed with the RNA-seq technology.ResultsA total of 11,7695 unigenes were assembled and 19,652 differentially expressed genes (DEGs) were obtained. The results showed that 1,716 DEGs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…NADH dehydrogenase (ubiquinone), oxidoreductase, and photosynthetic electron transport play a crucial role in energy production and conversion, in which the proteins are components in the mitochondrial respiratory chain. This showed that mitochondrial respiratory-related enzymes play an important role in the regulation of the CMS line C2P5A, and this result is consistent with a previous study in CMS plants [85][86][87]. Pectinesterase is a wall-degrading enzyme, and abnormal expression may lead to the disruption of the cell wall structure in the CMS line C2P5A; a previous study demonstrated that pectinesterase plays a major role in the plant [88].…”
Section: Lncrna In the Anther Development Of Cotton And Predicted Funsupporting
confidence: 91%
See 1 more Smart Citation
“…NADH dehydrogenase (ubiquinone), oxidoreductase, and photosynthetic electron transport play a crucial role in energy production and conversion, in which the proteins are components in the mitochondrial respiratory chain. This showed that mitochondrial respiratory-related enzymes play an important role in the regulation of the CMS line C2P5A, and this result is consistent with a previous study in CMS plants [85][86][87]. Pectinesterase is a wall-degrading enzyme, and abnormal expression may lead to the disruption of the cell wall structure in the CMS line C2P5A; a previous study demonstrated that pectinesterase plays a major role in the plant [88].…”
Section: Lncrna In the Anther Development Of Cotton And Predicted Funsupporting
confidence: 91%
“…Significant KEGG pathways were primarily enriched for several processes, such as fatty acid biosynthesis, flavonoid biosynthesis, glutathione metabolism, MAPK signaling pathway to the plant, oxidative phosphorylation, ubiquinone and other terpenoid quinone biosynthesis, pentose and glucuronate interconversions, and plant hormone signal transduction ( Figure 6A-C). Previous studies show that these metabolism pathways play a vital role during anther development in flowering plants, in which a disturbed metabolism pathway seriously leads to the impairment of anther development, and causes male sterility [55,57,61,62,85,89]. This study showed that some lncRNAs and mRNAs might play important roles in anther development, such as cis-target gene Ghir_A09G011050.1 of LTCONS_00105434 through GO:0008137 (NADH dehydrogenase (ubiquinone) activity) and ko00190 (oxidative phosphorylation); cis-target gene Ghir_A01G005150.1 of LTCONS_00004262 through GO:0016491 (oxidoreductase activity) and ko00941 (flavonoid biosynthesis); cis-target gene Ghir_D05G003710.2 of LTCONS_00126105 through GO:0005975 (carbohydrate metabolic process) and ko00040 (pentose and glucuronate interconversions); cis-target gene Ghir_A03G016640.1 of LTCONS_00085561 through GO:0016790 (catalytic activity) and ko00061 (fatty acid biosynthesis); and cis-target gene Ghir_A12G005100.1 of LTCONS_00085561 through GO:0005524 (ATP binding) and ko04016 (MAPK signaling pathway to the plant).…”
Section: Lncrna In the Anther Development Of Cotton And Predicted Funmentioning
confidence: 99%
“…With the advancement in genomics and transcriptomics studies, the effort has been made ease in identifying molecular marker linked to the Rf-genes which promote the integration of Rf-genes in various eggplant genetic backgrounds. Recently, comparative transcriptome analysis has been performed to identify the MS-related genes and pathway in the eggplant of the male sterile line and its maintainer line [103]. The finding of this study provided insight into key genes and pathways associated with eggplant male sterility, which provided a primary basis for further research on fertility and anther development.…”
Section: Prospects Of Male Sterility In Eggplant Heterosismentioning
confidence: 85%
“…Understanding the molecular mechanisms controlling anther development and male sterility is of great importance for heterosis utilization in many crop species, including cotton. In recent years, male sterility lines have been widely studied by transcriptomic analysis in different species, such as wheat [56,57], maize [58], eggplant [59] and cotton [60][61][62][63]. However, most studies tend to carry out extensive enrichment of DEGs without systematic classi cation analysis based on different development stages.…”
Section: Discussionmentioning
confidence: 99%